Clinical Results in Medullary Thyroid Carcinoma Suggest High Potential of Pretargeted Immuno-PET for Tumor Imaging and Theranostic Approaches - Bodet-Milin, Caroline; Bailly, Clément; Touchefeu, Yann; Frampas, Eric; Bourgeois, Mickael; Rauscher, Aurore; Lacoeuille, Franck; Drui, Delphine; Arlicot, Nicolas; Goldenberg, David M.; Faivre-Chauvet, Alain; Barbet, Jacques; et al. (Frontiers in Medicine, 2019)
Monoclonal antibody (mAb)-based therapies have experienced considerable growth in cancer management. When labeled with radionuclides, mAbs also represent promising probes for imaging or theranostic approaches. Initially, mAbs have been radiolabeled with single-photon emitters, such as 131I, 99mTc or 111In, for diagnostic purposes or to improve radioimmunotherapy (RIT) using dosimetry estimations. Today, more accurate imaging is achieved using positron- emission tomography (PET). Thanks to the important technical advances in the production of PET emitters and their related radiolabeling methods, the last decade has witnessed the development of a broad range of new probes for specific PET imaging. Immuno-PET, which combines the high sensitivity and resolution of a PET camera with the specificity of a monoclonal antibody, is fully in line with this approach. As RIT, immuno-PET can be performed using directly radiolabeled mAbs or using pretargeting to improve imaging contrast. Pretargeted immuno-PET has been developed against different antigens, and promising results have been reported in tumor expressing carcinoembryonic antigen (CEA; CEACAM5) using a bispecific mAb (BsmAb) and a radiolabeled peptide. Medullary thyroid carcinoma (MTC) is an uncommon thyroid cancer subtype which accounts for less than 10% of all thyroid neoplasms. Characterized by an intense expression of CEA, MTC represents a relevant tumor model for immuno-PET. High sensitivity of pretargeted immunoscintigraphy using murine or chimeric anti-CEA BsMAb and pretargeted haptens-peptides labeled with 111In or 131I were reported in metastatic MTC patients 20 years ago. Recently, an innovative clinical study reported high tumor uptake and contrast using pretargeted anti-CEA immuno-PET in relapsed MTC patients. This review focuses on MTC as an example, but the same pretargeting technique has been applied with success for clinical PET imaging of other CEA-expressing tumors and other pretargeting systems. In particular, those exploiting bioorthogonal chemistry also appear interesting in preclinical animal models, suggesting the high potential of pretargeting for diagnostic and theranostic applications.